Decision support method to systematically evaluate first-level inspections of the functional status of check dams. Issue 11 (1st November 2016) - Cortes Arevalo, Vivian Juliette; Sterlacchini, Simone; Bogaard, Thom A.; Junier, Sandra; van de Giesen, Nick
Abstract: First-level inspections could be provided by skilled volunteers or technicians to pre-screen the functional status of check dams. This paper discusses the design and testing of a support method in collaboration with the responsible technicians in evaluating inspection reports. Reports are based on linguistic rating scales that are systematically aggregated into indices by means of a multi-criteria TOPSIS method with fuzzy terms. The aggregation procedure is carried out for three parameters representing the structure's status while highlighting any lack of completeness of inspection reports. The method was evaluated using inspection reports collected during a workshop in the Fella basin in the Italian Alps. The method allows the responsible technicians to set rules to categorise the aggregated indices in one of three levels, each corresponding with a course of action. Rules were useful to categorise the aggregated indices according to the structure's status. Disagreements on rating defects suggest that a weighted aggregation procedure to calculate the indices might lead to overestimating or underestimating defects. Complementary data from historical inspections or remote sensing are required to initiate specific actions. The method can be applied to pre-screen different types of hydraulic structures after adaptation to the local conditions and functional requirements.